The effect of acromegaly on thyroid disease - Caiyan Mo; Liyong Zhong (Endocrine Journal)
Long-term stimulation of thyroid follicular epithelium by high growth hormone (GH) and insulin-like growth factor-1 (IGF-1) in patients with acromegaly can lead to thyroid dysfunction, goiter, thyroid nodules, and even thyroid cancer and thyroid-associated ophthalmopathy (TAO). Excessive GH/IGF-1 promotes goiter and thyroid nodule formation, which can be reversed by normalizing the IGF-1 levels with surgery or medical treatment. Whether patients with acromegaly have an increased risk of thyroid cancer remains controversial, and routine thyroid ultrasonography and regular cancer screening are recommended in such cases, especially when the nodules possess malignant propensity. TAO is an autoimmune disease and newer treatments are being discovered against it. Recent studies have reported that the IGF-1 receptor (IGF-1R) plays an important role in the pathogenesis of TAO, and the IGF-1R inhibitor teprotumumab involves significantly improved disease endpoints in patients with active TAO. Thyroid-stimulating hormone (TSH) receptor (TSHR) and IGF-1R co-immunoprecipitate in orbital and thyroid tissues to form a functional complex; thus, combined therapy targeting TSHR and IGF-1R may be more effective than single therapy.